The History of Curriculum in Indonesia: A Literature Study - Rani Oktavia; Akhmad Ali Mirza; Zaitun Qamariah (BADAN PENERBIT STIEPARI PRESS, 2023)
To accomplish national educational goals, the curriculum is a collection of ideas and arrangements for learning activities. It includes of topics covered in numerous disciplines and issues from daily life. There are three functions played by the curriculum: conservative, critical or evaluative, and creative. While critical or evaluative roles preserve values and cultural pasts for pupils, conservative roles impart cultural heritage values that are pertinent to the present. In order to address society's future demands, creative jobs participate in productive and innovative activities that produce new knowledge, insights, and abilities. The